Goat kids fed diets containing castor cake detoxified: II. Nitrogen balance, hepatic and renal function - Araújo, Ricardo Alves de; Pompeu, Roberto Cláudio Fernandes Franco; Rogério, Marcos Cláudio Pinheiro; Cândido, Magno José Duarte; Neiva, José Neuman Miranda (Acta Scientiarum. Animal Sciences, 2022)
The aim of this study was to evaluate the influence of completely replacing soybean meal (SM) with castor cake detoxified (DCC) with two alkaline products on the nitrogen balance and hepatic and renal function in goat kids. Goat kids of two breeds, Saanen and Anglo Nubian, with an initial body weight of 16.2 ± 0.67 kg, and confined during the growth phase, were used. The treatments consisted of three diets: one based on SM and the other two based on castor cake detoxified with Ca(OH)2 or NaOH. Twenty-four goats kids were distributed in a completely randomized design using a 3 x 2 factorial scheme (diet x breed) with four replicates per combination. The experimental period lasted for 270 days. Consumed nitrogen, fecal nitrogen, urinary nitrogen, retained nitrogen, and nitrogen balance were influenced (p < 0.05) by diets. There was significant effect of diets (p < 0.05) on creatinine, direct bilirubin, urea, alanine aminotransferase, aspartate aminotransferase and gamma-glutamyltransferase blood levels, however without any negative changes involving renal or hepatic dysfunction. Inclusion of castor cake in the diet of goats kids in confinement is an attractive option, considering that goats kids use does not cause hepatic and renal alterations, suggesting that SM can be completely replaced. NaOH DCC stands in the substitution of soybean meal, because in spite of decreasing the consumption of nitrogen provides the same retention of soybean meal.